2020
DOI: 10.31575/jp.v3i3.195
|View full text |Cite
|
Sign up to set email alerts
|

Mekanisme Good Corporate Governance Dan Leverage Terhadap Kinerja Keuangan Perbankan

Abstract: This study aims to examine the mechanism of Good Corporate Governance And Leverage On Banking Financial Performance. the population is a banking company registered on the IDX in 2016, which is 43 companies. The sample collection technique has been done using a purposive sampling method and based on predetermined criteria, 8 companies have been selected as samples. The company's financial report data has been obtained from the official IDX website. The analytical method used is panel data regression analysis wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 1 publication
1
3
0
Order By: Relevance
“…Because to report high profits, managers must reduce costs so that leverage affects financial performance. The results of this study support previous research conducted by [27], [24], [31], [28], [30], (Aiman & Rahayu, 2019), [26], [48], [49], [50],…”
Section: The Effect Of Leverage On Financial Performancesupporting
confidence: 91%
See 3 more Smart Citations
“…Because to report high profits, managers must reduce costs so that leverage affects financial performance. The results of this study support previous research conducted by [27], [24], [31], [28], [30], (Aiman & Rahayu, 2019), [26], [48], [49], [50],…”
Section: The Effect Of Leverage On Financial Performancesupporting
confidence: 91%
“…So it can be concluded that the implementation of good corporate governance indirectly affects the increasing financial performance (ROA) of banks. [53], [26], [17], [27], [24].…”
Section: Icesrementioning
confidence: 99%
See 2 more Smart Citations